The role of cystatin C, neutrophil-lymphocyte ratio and platelet-lymphocyte ratio in the evaluation of kidney function in women with preeclampsia - Aysun Tekeli Taşkömür; Özlem Erten (Elsevier, 2021)
Objective: We aimed to compare the diagnostic efficiency of cystatin C with traditional kidney markers in preeclampsia and to evaluate the relationship of these markers with neutrophil-lymphocyte and thrombocyte-lymphocyte ratios. Materials and methods: 14 severe preeclampsia, 48 mild preeclampsia and 79 patients with healthy pregnancy who presented to our obstetrics and gynecology clinic within one year were compared. These three groups were compared in terms of demographic characteristics, physical findings, serum urea, creatinine, cystatin C levels, and neutrophil-lymphocyte and platelet-lymphocyte ratios. Results: The mean serum cystatin C, creatinine and uric acid levels were higher in the severe preeclampsia group compared with the mild preeclamptic and healthy pregnancies (p < 0.001). While cystatin C values increased as the week of gestation increased in the mild preeclampsia group, there was no relation with the gestational week in the control group and the severe preeclampsia group. However, the highest cystatin C values were in the severe preeclampsia group, regardless of the week (p < 0.05). The area under the ROC curve was statistically significant for cystatin C, uric acid and creatinine, but of these three values, cystatin C had the highest sensitivity and specificity. Neutrophil-lymphocyte ratio (NLR) was significantly higher in the severe preeclampsia group than healthy pregnancies, but the level was not significant compared to mild preeclampsia. There was no difference between the groups in terms of platelet-lymphocyte ratio. Conclusion: It can be suggested that cystatin C level reflects renal functions better than uric acid and creatinine in preeclampsia. Cystatin C can be used as a prognostic marker in preeclamptic pregnancies, and rising levels may be valuable for predicting severe preeclampsia. Especially with advancing gestational week, the increase in cystatin C level may indicate an association with the development of preeclampsia. NLR levels may be a parameter correlating with severity in severe preeclampsia.